THE REPERCUSSIONS OF CARDIOVASCULAR ILLNESSES: CASE HISTORY - Karyna Turra; Carla Trentin; Debora S Ribeiro; Maria de Fátima Mantovani; Ymiracy do Nascimento de Sousa Polak (Universidade Federal do Paraná, 2001)
It is a case history of an extension project of Federal University of Parana named "The Adult with Cardiovascular Problems and the Process of Identity Remaking to Cope with Chronicity", whose goal was to identify the change repercussions in the daily lives of individuals presenting cardiovascular problems admitted at a hospital in the Metropolitan Area of Curitiba/ Parana - Brazil. An instrument for data collection, previously tested, was devised to undertake this study, being applied under the ethical procedure of informed consent, two afternoons a week during the year 2000. Twenty-two (22) clients participated in this study: 14 men and 8 women, ranging from 27 and 75 years of age, being visited before and after surgeries. Changes in their daily lives were ultimately related to work and physical exercises, food and smoking habits, family support being stressed to cope with these problems. The results of this study point out the peer groups which aim at promoting life quality to clients with chronic health problems and further experience and information exchange among people who have gone through similar situations.